Rock art imagery as a proxy for Holocene environmental change: A view from Shuwaymis, NW Saudi Arabia. (November 2016) - Guagnin, Maria; Jennings, Richard; Eager, Heidi; Parton, Ash; Stimpson, Christopher; Stepanek, Christian; Pfeiffer, Madlene; Groucutt, Huw S.; Drake, Nick A.; Alsharekh, Abdullah; Petraglia, Michael D.
The animal species depicted in the rock art of Shuwaymis, Saudi Arabia, provide a record of Holocene climatic changes, as seen by the engravers. Of 1903 animal engravings, 1514 contained sufficient detail to allow identification with confidence. In addition, the stratigraphy of the engravings and the depiction of domesticates provide a broad chronological framework that allows a division into images created during the Holocene humid phase and animals represented after the onset of desert conditions. Despite the large sample size, only 16 animal species could be identified, which represents an extraordinarily narrow species spectrum. Comparison with the scarce faunal record of the Arabian Peninsula shows that all larger animals that are thought to have been present in the area were also depicted in the rock art. The contemporaneous presence of at least four large carnivores during the Holocene humid phase suggests that prey animals were abundant, and that the landscape consisted of a mosaic of habitats, potentially with thicker vegetation along the water courses of the wadis and more open vegetation in the landscape around them. Community Earth System Models (COSMOS) climate simulations show that Shuwaymis was at the northern edge of the African Summer Monsoon rainfall regime. It is therefore possible that Shuwaymis was ecologically connected with southwestern Arabia, and that an arid barrier remained in place to the north, restricting the dispersal of Levantine species into Arabia.